Race in the age of Obama - Cunnigen, Donald; Bruce, Marino A. (Research in race and ethnic relations ;, 2010)
This volume provides the first in-depth examination of the impact of the key sociological issues faced by the new Obama Administration and explores conventional topics on race and ethnic relations as well as delves into new areas of intellectual inquiry regarding the changing scope of race relations in a global context. Leading scholars look at: African/American relations through the prism of American and African scholars; the connection between religion, Obama the individual and Obama the President; how the Obama election and presidency have implications for gender identity and sexual politics in the short and long term; the impact the Obama family and their presence in the White House have on existing ideas about the concept of family and related issues; implications for class relations in the United States; specific aspects of the American educational system; social justice issues with an emphasis on understanding their sociological context in relationship to the Obama Administration; and American involvement in the Iraq and Afghanistan War. In addition, the volume examines the 2008 Presidential Election, with emphasis on Obamas road to success.